ANALISIS FAKTOR PENYEBAB KURANGNYA KEMAMPUAN SISWA DALAM BACA TULIS AL-QUR’AN DI MTsN KEDURANG BENGKULU SELATAN - - Gusman (IAIN Bengkulu, 2017)
Problems faced in the learning process and what efforts are made in tackling obstacles in learning to read Al-Quran in MTs N Kedurang South Bengkulu. In this study data collection is done through interviews, observation and documentation, with informants are the Head of School, Waka Curriculum and Al-Qur’an reading teacher in MTs Negeri Kedurang. While to analyze data using qualitative descriptive analysis technique, that is descriptive and menginterprestasikan data that have been obtained so that will depict reality that actually in accordance with existing phenomenon. The results of this study indicate Factors that inhibit the study of the Koran in accordance with among others: (a) Less fulfillment of books and supporting learning media (b) Minimnya time of religious learning, especially the Koran. (C) The level of student ability varies. Problematic faced by teachers are: a. Level of knowledge of students who are not the same, b. The limited hours of teaching, c. The use of teaching methods in traditional learning makes students quickly bored. D. Evaluation of the affective and psychomotor domains is rarely done due to limited time and facilities. As for efforts to improve the literacy of Al-Qur’an students are: a. Increase hours of recitation after school hours after b. Conducting cooperation with TPA in the area of origin of each student. C. Creating good conditions during the teaching and learning process. D. Completing facilit i es and infrastructure of learning Al-Qur’an In MTs Negeri Kedurang